Studi Analisis Putusan Hakim tentang Tindak Pidana Penadahan pada Masa COVID-19 Perspektif Hukum Pidana Islam di Pengadilan Negeri Tanjung Pati (Periode Perkara 2019-2023) - Zelfani Zazkia Reginal; Hendri Hendri (Lembaga Yasin AlSys, 2026)
The criminal offense of receiving stolen goods constitutes a form of property crime that causes losses to victims and disrupts legal order, and during the Covid-19 pandemic, shifting social dynamics contributed to an increase in such cases within the jurisdiction of the Tanjung Pati District Court. This study aimed to examine judges’ considerations in decisions on cases of receiving stolen goods at the Tanjung Pati District Court during the pandemic and to analyze these considerations from the perspective of Islamic criminal law. A field research design with a qualitative approach was employed. Data were collected through in-depth interviews with judges, document analysis of 21 court decisions on receiving stolen goods, and a review of the Indonesian Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), and Islamic legal literature, then analyzed through the stages of data reduction, data display, and verification. The findings show that judicial decisions in cases of receiving stolen goods during the Covid-19 pandemic took into account juridical, sociological, philosophical, and subjective aspects as an effort to realize substantive justice under exceptional social conditions. From the perspective of Islamic criminal law, the offense of receiving stolen goods is classified as jarimah hirabah punishable by taʿzir, whereby the determination of sanctions is left to the judge’s ijtihad. Accordingly, the imposition of imprisonment in these decisions is consistent with the values and objectives of Islamic criminal law. This study recommends the need for closer synchronization between positive law and the values of Islamic criminal law in handling cases of receiving stolen goods, particularly in emergency situations such as a pandemic, in order to produce decisions that are more just and oriented toward public welfare.